Development of tasty marinating kit for tenderization and preservation of beef chuck (Bangladesh Veterinarian, 2010)
Chuck is the biggest and one of the tougher cut of beef carcass. By improving the tenderness of chuck meat it can have a higher value to the consumer. The study was conducted to know the efficacy of tasty kit (containing 1.2 M sodium chloride, 0.25 M sodium bicarbonate and 0.1% ascorbic acid) as a meat preservation and tenderization technique during freezing. Beef chucks from four native bulls were collected from a local market and divided into two groups- one was treated with tasty kit and the other kept as control. Both the treated and untreated meats were well packed and kept in freezer at -20°C for a month. Compared to the untreated group, higher moisture content was found in treated raw and cooked meat (p